2015
DOI: 10.5194/acp-15-5683-2015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of fresh and aged secondary organic aerosol from a mixture of biogenic volatile compounds: a high-resolution mass spectrometry study

Abstract: Abstract. Field observations over the past decade indicate that a significant fraction of organic aerosol in remote areas may contain highly oxidized molecules. Aerosol processing or further oxidation (aging) of organic aerosol has been suggested to be responsible for their formation through heterogeneous reaction with oxidants and multigenerational oxidation of vapours by OH radicals. In this study we investigated the influence of several aging processes on the molecular composition of secondary organic aeros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 63 publications
12
100
1
Order By: Relevance
“…MW 358 and 368 esters were first reported in ambient nighttime PM with an aerodynamic diameter ≤ 2.5 µM (PM 2.5 ) that was collected at K-puszta, Hungary, during a 2006 summer campaign (Yasmeen et al, 2010). They were later detected in several field studies that were conducted in other forested environments (Kristensen et al, 2013(Kristensen et al, , 2016Kourtchev et al, 2014Kourtchev et al, , 2015. It was shown by Kourtchev et al (2016) that oligomers (i.e., hetero-oligomers) are of climatic relevance in that elevated SOA mass is one of the key drivers of oligomer formation not only in laboratory experiments but also in the ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…MW 358 and 368 esters were first reported in ambient nighttime PM with an aerodynamic diameter ≤ 2.5 µM (PM 2.5 ) that was collected at K-puszta, Hungary, during a 2006 summer campaign (Yasmeen et al, 2010). They were later detected in several field studies that were conducted in other forested environments (Kristensen et al, 2013(Kristensen et al, , 2016Kourtchev et al, 2014Kourtchev et al, , 2015. It was shown by Kourtchev et al (2016) that oligomers (i.e., hetero-oligomers) are of climatic relevance in that elevated SOA mass is one of the key drivers of oligomer formation not only in laboratory experiments but also in the ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Under supersaturated conditions, aqueous chemistry occurring in cloud and fog droplets promotes the conversion of small water-soluble molecules into nonvolatile products that would not form in the absence of liquid water (Herrmann et al, 2015). Finally, dissolved SOA compounds may undergo more efficient photodegradation in water (Bateman et al, 2011;Nguyen et al, 2012;Romonosky et al, 2015Romonosky et al, , 2017Zhao et al, 2017) compared to dry particles (Kourtchev et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The negative ionization mass spectra were collected in three replicates over ranges m/z 100-650 and m/z 150-900 and processed using Xcalibur 2.1 software (Thermo Scientific). Chemical formulae of the form C c H h N n O o S s were made according to analysis procedures presented in Kourtchev et al (2013Kourtchev et al ( , 2015 and Zielinski et al (2018), and only ions that were observed in all three replicate extract analyses were kept for evaluation. All sample intensities were normalized to the aerosol organic carbon loading as well.…”
Section: Nanoelectrospray (Nanoesi) Ultrahigh-resolution Mass Spectromentioning
confidence: 99%